PERSUASIVE AND EDUCATIVE ADVERTISING CONTENT OF QUICK RESPONSE CODE INDONESIAN STANDARD IN PANDEMIC ERA - Kristanti, Evelyn; Marta, Rustono Farady (Jurnal Ilmu Sosial dan Humaniora, 2021)
The digital payment system had increased rapidly, especially when Corona Virus Disease (COVID-19) entered Indonesia. Increasing technological advances have shifted people's preference towards cashless transaction activities. These days, money is known to have spread viruses such as COVID-19. In order to support the National Economic Recovery program, Bank Indonesia (BI) developed Contactless QRIS, which allows users to make contactless payments with merchants during the COVID-19 pandemic. BI positions its products in the eyes of consumers by using the internet and YouTube social media as a platform that plays a vital role in framing society's paradigm towards a reality, thus influencing people's attitudes. The research problem is aimed to know and analyze the content analysis of advertising "Using Contactless QRIS Practically" on the BI YouTube channel. This study aimed to analyze the content of BI advertising entitled "Using Contactless QRIS Practically." Researchers used Means-End Chain (MEC) Theory. This study used descriptive qualitative research with the content analysis method. The research has shown that based on content analysis, this advertising was persuasive and educative.